Bilateral agreement for the academic year 2007-2010 LLP Programme: higher education (Erasmus) between National and Kapodistrian University of Athens and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Erasmus programme; - Erasmus subject area: Law.